Ethanol Extract Test of Mustajab Leaves (Rhinacanthus nasutus L. Kurz) Against the Growth of Fusarium oxysporum - Lalu Septiadi Wirandanu; Syamsul Bahri; Dewa Ayu Citra Rasmi (Jurnal Biologi Tropis, 2022)
The research goal is to analyze the concentration of ethanol extract of mustajab (Rhinacanthus nasutus) leaves which is has the most effective in inhibiting the growth of Fusarium oxysporum micelium which were isolated from shallots (Alliun cepa L). The sample testing method used the method of effectiveness. The experimental design used Completely Randomized Design (CRD). The data of inhibition acitivity of ethanol extract of mustajab (Rhinacanthus nasutus) leaves on the growth of Fusarium oxysporum were collected by measuring the diameter of the mycelium of Fusarium oxysporum. The data of inhibition acitivity were analyzed by using a one-way analysis of variance at a significance level of 95%, followed by the Honestly Significant Difference test. The results showed that concentrations of ethanol extract of mustajab (Rhinacanthus nasutus) leaves significantly effective in inhibiting the growth of Fusarium oxysporum mycelium. The most effetive concentration of ethanol extract of mustajab (Rhinacanthus nasutus) leaves in inhibiting the growth of Fusarium oxysporum is 5%. The inhibition activity of this concentration is up to 64%, and this inhibition activity is classified into the strong category.